PLASTICIZATION EFFECTS OF ETHALINE DEEP EUTECTIC SOLVENT VERSUS GLYCEROL ON THERMOPLASTIC STARCH FILMS FROM CASSAVA PEELS - Musa, Qasim; Tajudeen, Kolawole Bello; Jaju, Abubakar Muhammad; Alewo, Opauda Ameh (FUDMA Journal of Sciences, 2026)
The plasticization efficiency evaluation of deep eutectic solvent (DES), based on choline chloride (CC) and ethylene glycol has been performed on the extracted starch from cassava peels as compared to the conventional plasticizer glycerol in the production of thermoplastic starch (TPS) (bioplastic films). In this work, Deep eutectic solvents (Ethaline) was evaluated as plasticizer and it’s plasticization effect was compared with glycerol at varying concentrations (0, 5, 10, 15, 20, 25 and 30 wt%). The mechanical testing portrayed that Ethaline plasticized thermoplastic starch (TPS) exhibited higher tensile strength of 3.9 MPa at low concentrations (15 wt%) compared to glycerol 3.1 MPa, while maintaining acceptable elongation. At higher concentration (>20 wt%), Ethaline enhanced flexibility but reduced tensile strength similar to glycerol. Water absorption studies revealed that Ethaline plasticized-TPSs absorbed less moisture than glycerol counterpart, suggesting improved barrier properties. Overall, Ethaline has a good potential of plasticization and inhibits the migration of plasticizer from the polymer matrix, compare to conventional ones like glycerol, as it improves the performance of bioplastic films (TPSs) in both mechanical and barrier properties.
Keywords: plasticization; thermoplastic starch; deep eutectic solvent; Ethaline and glycerol